2015
DOI: 10.1002/2014gc005566
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of MORB and plume mantle volatile budgets: Constraints from fission Xe isotopes in Southwest Indian Ridge basalts

Abstract: We present high-precision measurements of the fission isotopes of xenon (Xe) Xe is recycled in origin), consistent with results from studies of plume-influenced basalts from Iceland and the Rochambeau Rift. While significant regassing of the mantle is evident, we also find differences in the extent of degassing of the MORB and plume sources. MORB sources are consistently characterized by a lower fraction of fission Xe derived from Pu-fission, indicating a greater extent of degassing relative to the plume sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 68 publications
(213 reference statements)
2
40
0
Order By: Relevance
“…Even if recycling of heavy noble gases (Ar, Kr, Xe) through subduction may occur (Holland and Ballentine, 2006;Kendrick et al, 2011;Parai and Mukhopadhyay, 2015), recycling of He and Ne into the OIB gas-rich source is not significant (Staudacher and Allègre, 1988;Holland and Ballentine, 2006). The 20 Ne/ 22 Ne ratio of 12.65 ± 0.04 is thus likely to represent the Fernandina source isotopic composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if recycling of heavy noble gases (Ar, Kr, Xe) through subduction may occur (Holland and Ballentine, 2006;Kendrick et al, 2011;Parai and Mukhopadhyay, 2015), recycling of He and Ne into the OIB gas-rich source is not significant (Staudacher and Allègre, 1988;Holland and Ballentine, 2006). The 20 Ne/ 22 Ne ratio of 12.65 ± 0.04 is thus likely to represent the Fernandina source isotopic composition.…”
Section: Discussionmentioning
confidence: 99%
“…The air component may be derived from post-eruption contamination when samples are recovered from the seafloor (Ballentine and Barfod, 2000). It may also come from atmospheric recycling through subduction for heavy noble gases (Ar, Kr, Xe) (Holland and Ballentine, 2006;Kendrick et al, 2011;Parai and Mukhopadhyay, 2015). Noble gas studies often use step-crushing to analyse samples, and the results yield mixing trends between an atmospheric end-member and a mantle end-member.…”
Section: Introductionmentioning
confidence: 99%
“…The parent isotopes, 129 I and 244 Pu, are short-life, so that they had decayed into the daughter species, 129 Xe(I) and 136 Xe(Pu), during the early Earth's evolution. Caracausi et al [2016] and Parai and Mukhopadhyay [2015] showed that this early generated ratio in MORB, 129 Xe(I)/ 136 Xe(Pu)≈ 8, is somewhat higher than in the plume rocks, ≈ 2. Figure 2.…”
Section: Nucleogenic Xenon Isotopes In the Mantlementioning
confidence: 94%
“…Precise measurements of the isotopic composition of Xe in mantle rocks and gases allowed 136 Xe(Pu) and 136 Xe(U) to be distinguished in samples of mantle plume and mid-ocean ridge basalts, but also in carbon dioxide gases [Ballentine and Holand, 2008;Caracausi et al, 2016;Parai and Mukhopadhyay, 2015]. The parent isotopes, 129 I and 244 Pu, are short-life, so that they had decayed into the daughter species, 129 Xe(I) and 136 Xe(Pu), during the early Earth's evolution.…”
Section: Nucleogenic Xenon Isotopes In the Mantlementioning
confidence: 99%
See 1 more Smart Citation